Phenotyping of Urochloa humidicola grass hybrids for agronomic and environmental performance in the Piedmont region of the Orinoquian savannas of Colombia. (12th October 2022) - Villegas, Daniel M.; Arévalo, Ashly; Sotelo, Mauricio; Nuñez, Jonathan; Moreta, Danilo; Rao, Idupulapati; Ishitani, Manabu; Subbarao, Guntur V.; Arango, Jacobo
Abstract: In the low fertility acid soils of the Orinoquian savannas of Colombia, Urochloa humidicola cv. Tully or Humidicola is one of the most widely planted tropical forage grasses for improving livestock productivity. Low nutritional quality of this grass limits sustainable livestock production in this region. In this study, we conducted a phenotypic evaluation under field and greenhouse conditions of one of the first hybrid populations of U. humidicola generated from the forage breeding program of CIAT. Our objective was to identify a set of new hybrids of U. humidicola that combine improved productivity and nutritional quality plus the biological nitrification inhibition (BNI) trait/ability to reduce nitrogen (N) losses via leaching and nitrous oxide (N2 O) emissions. To this end, we tested 118 hybrids (planted in pots) in the greenhouse for over 6 months and measured potential nitrification rates (NR) using soil microcosm incubation. NR values observed ranged from 0.27 to 5.75 mg N‐NO3 − kg soil −1 day −1 . Later, 12 hybrids with different levels of NR were selected and field‐tested in the Orinoquia region over a 4 years period (2013–2017) for dry matter production, nutrition quality (crude protein, in vitro digestibility and fibres content) and NR in each year. In the rainy season of 2018, two hybrids with superior agronomic performance and contrasting field level NR (Uh08/1149 and 0450) were subjected to analysis of soil‐borne N2 O emissions after fertilization during 13 days. The NR values recorded were not directly correlated with the forage quality parameters evaluated, however, the two grasses with the lowest NR values were among those with the highest biomass production, crude protein content, and N uptake. The grass hybrid Uh08/1149 and the germplasm accession CIAT 16888 were found as materials with superior forage value, with production of 14.1 and 14.6 tons dry matter ha −1 year −1 (up to 8% higher than the cv. Tully), crude protein of 11.5 and 9.1% per cut (up to 20% higher than the cv. Tully), and N uptake of 31.6 and 25.7 kg N ha −1 cut −1 (up to 30% higher than the cv. Tully). Additionally, these two grasses are likely to exhibit high‐BNI ability, with potential to improve N use efficiency in managed pastures.